New diazo coupling of metoclopramide with 2,6-dimethyl phenol after using cloud point extraction method - Fadhel, Suha Nasser (Pharmakeftiki, 2025)
An environmentally safe spectroscopic technique has been developed for the determination of metoclopramide (MCP) in pharmaceutical samples. This method is rapid, practical, and suitable for the analysis of MCP both in its pure form and within pharmaceutical preparations, with or without the application of point cloud extraction technology. The procedure involves the nitration of metoclopramide at 5°C using sodium nitrite, followed by its reaction with 4-nitrophenol in an alkaline medium in order to yield a purple-coloured product. All experimental variables were optimized a priori so as to achieve robust and reproducible results. After stabilization of the chromophore, absorbance measurements were performed at 440 nm. Within the concentration range of 1–12 µg×mL-1, the method adhered to Beer’s law.